The chicken house - Cronin, Doreen (Cronin, Doreen. Chicken Squad., 2021)
Sugar, Dirt, Sweetie, Poppy, and their mother, Moosh, live in a crowded chicken house until Sugar ventures out and finds a new home with a bathtub, a large bed, and even a massage table.